Analysis Of The Cause Of The Imperfect Process Of Fogging The Injector Of The Main Engine On The Ship KMP. Trimas Laila - Miran, Miran; Tungkup, Doharman Lumban; Marcelo Lopulalan, Pierre (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
One of the components contained in the main motor, which affects the combustion system is the injector. The smog of fuel into the combustion chamber is determined by whether or not the condition of the nozzle on the injector is good. If the middle nozzle is in a state of constraint, the nozzle cannot atomize the fuel optimally. If that happens, the combustion process will also be disrupted and will affect the power of the engine. The method carried out at this KKW uses data collection techniques by direct observation during maintenance and direct interviews from people who know on the ship, with the aim of knowing the cause of the imperfection of the injector fogging process on the main engine on the ship, it will affect the injection and fogging system on the ship. ship so that it can be known what factors are the cause of the problem. Based on the results of research that has been carried out on the KMP. Trimas Laila, it can be concluded that what affects the imperfection of the fogging process on the injector is the clogged nozzle hole and the dripping of fuel at the tip of the nozzle. from this it can result in the engine not reaching maximum speed and irregular exhaust gas which initially reached 360oc to 440oc, after treatment the exhaust gas temperature returned to normal to 360 oc.